Effects of leaf removal and cluster thinning on berry quality of Vitis vinifera cultivars in the region of Weibei Dryland in China - Chang-zheng SONG; Chao WANG; Sha XIE; Zhen-wen ZHANG (Journal of Integrative Agriculture, 2018)
Leaf removal and cluster thinning were carried out prior to veraison to evaluate the effects on berry quality of two Vitis vinifera cultivars (Cabernet Sauvignon and Ugni Blanc) in the Weibei Dryland of China in 2013 and 2014, and comprehensive analysis of the chemical and volatile composition in berries was performed. The results showed that content of reducing sugar in both varieties was not affected while total acid was generally decreased by leaf removal and cluster thinning. The pH of berry juice was correspondingly higher in most treatment groups. Meanwhile, promoting effects on accumulation of total phenols, tannin in both varieties and total anthocyanins in Cabernet Sauvignon were found. As for monomeric anthocyanins, percentage of malvidin and its derivatives was decreased by leaf removal and cluster thinning. Besides, cinnamylated anthocyanins decreased with the intensity of cluster thinning. The accumulation of non-anthocyanin phenolics was similarly affected in the two varieties. Notably, cluster thinning was more effective on enhancing the phenolics content than leaf removal. The combination of middle level of leaf removal and cluster thinning was the most favor to the accumulation of phenolic acids. Furthermore, cluster thinning could also significantly enhance the synthesis of flavanols and stilbenes. Lastly, content and variety of aroma compounds in both grape varieties were also significantly affected by the treatments. The results provided a theoretical basis for a combination of leaf removal and cluster thinning to improve quality of grapes and wines.